Induced frustrated twist grain boundary liquid crystalline phases in binary mixtures of achiral hockey stick-shaped and chiral rod-like materials. Issue 34 (14th August 2019) - Chakraborty, Susanta; Das, Malay Kumar; Bubnov, Alexej; Weissflog, Wolfgang; Węgłowska, Dorota; Dabrowski, Roman
Abstract : Induction of TGB phases in binary mixtures of hockey stick-shaped and chiral ferroelectric liquid crystal compounds. Abstract : For a newly designed binary liquid crystalline system we report the induction of two stable twist grain boundary (TGB) phases, namely the orthogonal paraelectric TGB smectic A * (TGBA*) and tilted ferroelectric TGB smectic C* (TGBC*) phases, within a quite broad temperature range. The designed binary mixtures consist of a highly tilted chiral ferroelectric compound, ( S )(+)-4′-(ω-alkanoyloxy)alkoxybiphenyl-4-yl-4-(1-methylheptyloxy) benzoates (2H6R ) and an achiral hockey stick-shaped compound (H-22.5 ). Measurements of optical transmission intensity, static permittivity ( ε ‖, ε ⊥ ), spontaneous polarization ( P s ), torsional bulk viscosity ( η ) and dielectric spectroscopy have been carried out for all the mixtures and the pure chiral compound. Possible outcomes and related transitional phenomena have been discussed from the viewpoint of perturbation introduced by the achiral hockey stick-shaped molecules. Dielectric studies reveal a sign inversion (positive to negative) of the dielectric anisotropy for all the mixtures including the pure compound. By increasing the concentration of achiral hockey stick-shaped compound, it is possible to increase the temperature range of the positive dielectric anisotropy. On the other hand, the measured values of spontaneous polarization in the TGBC* phase for the mixtures are considerably lower than that of the SmC* phase for the compound2H6R ; conversely, the response time and effective torsional bulk viscosity for the mixtures possess a higher value than that of the SmC* phase of the pure2H6R compound. Additionally, the frequency-dependent dielectric spectroscopy measurement reveals that the relaxation frequency and dielectric strength of the Goldstone mode in the TGBC* phase slightly decreases compared to the SmC* phase of the pure compound due to the addition of theH-22.5 dopant.